Passos de Anchieta: a arte de caminhar com fé no Espírito Santo - Costa, Leide Bela de Brito Anália da (2009)
Through a reflection on the history and tradition of religion in Brazil, a legacy not only of the formative process of Brazilian society, but also of the current transformation, reordering and configuration process within Brazilian religiosity, this work seeks to understand the event The Way of Anchieta , also known as The Path of Anchieta , in the universe of Christian pilgrimages. The event reconstructs the historic path walked by father Anchieta in the region of Espírito Santo in the XVI century. In the context of this study, we understand that this walk is a most perfect metaphor for life: the trip we undertake in time, from the cradle to the grave. Thus, the walk teaches us to find ourselves in times of individual reflection, and to find others in the sharing of the same steps of the path. So an attempt will be made to understand how the ritualised experience undergone in life, is duplicated in the walk, reappraising everyday life and bringing new meaning to the experience of what is real and what is transcendent. Since the rote of the pilgrimage enriches this ritual, updating the experience of the walk in a pedagogic dimension where the pilgrimage as lived spatiality permits the reworking and transmission of the personal and collective experience as space even for new understandings of the human dimension. How do the participants in the The Way of Anchieta see the experience of walking the path and what meaning they attribute to it. The event here is understood to be hybrid space which is a result of the dynamic of a social process which permeates traditional and modern aspects and of the symbolic construction of principles and values which make the pilgrimage a renewed practice and an emergent channel for new practices and for new social actors, giving this phenomenon a new feel, value and meaning. Since the 90s, this dynamic has been gaining visibility in the Brazilian urban space. In the current context, the event has established itself as one more possibility for a topical rereading of Catholicism and of the Christian experience in the contemporary era. Our hypothesis is that the The Way of Anchieta acts as a reordering of social identities and outlines a new ethos of the impacting, both individual and collective insertion, on contemporary Capixaba society